2003
DOI: 10.1590/s1517-86922003000200004
|View full text |Cite
|
Sign up to set email alerts
|

Do continuous and intermittent exercises sets induce similar cardiovascular responses in the elderly women?

Abstract: There is a lack of information about elderly acute cardiovascular responses in the elderly during exercise involving different muscle groups and strategies of load/repetition interaction (LRI) in continuous and intermittent sets. The purpose of this study was to compare heart rate (HR), systolic blood pressure (SBP), rate-pressure product (RPP) and quality of exercise performance (QEx) of upper and lower body exercises (arms abduction and hip flexion) in different situations of LRI. Twelve healthy women aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…2005 Combined program - not PRT alone Thielman 2004 No relevant outcomes to the review Thomas 2004 Combined program - not PRT alone Thomas 2005 Training did not meet criteria for PRT - The resistance was not progressively increased Thompson 1988 Combined program - not PRT alone Timonen 2002 Combined program - not PRT alone Timonen 2006 Combined program - not PRT alone Timonen 2006b Combined program - not PRT alone Treuth 1994 Not a RCT Trudelle-Jack. 2004 Combined program - not PRT alone Tsuji 2000 Combined program - not PRT alone Vad 2002 Combined program - not PRT alone Vale 2003 Article cannot be identified Valkeinen 2005 Participants too young (mean age of the control group < 60) Van den Ende 2000 Combined program - not PRT alone Vanbiervliet 2003 Included young participants (younger than 60 years old) Veloso 2003 Does not meet the criteria for PRT Verfaillie 1997 Combined program - not PRT alone Villareal 2003 …”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…2005 Combined program - not PRT alone Thielman 2004 No relevant outcomes to the review Thomas 2004 Combined program - not PRT alone Thomas 2005 Training did not meet criteria for PRT - The resistance was not progressively increased Thompson 1988 Combined program - not PRT alone Timonen 2002 Combined program - not PRT alone Timonen 2006 Combined program - not PRT alone Timonen 2006b Combined program - not PRT alone Treuth 1994 Not a RCT Trudelle-Jack. 2004 Combined program - not PRT alone Tsuji 2000 Combined program - not PRT alone Vad 2002 Combined program - not PRT alone Vale 2003 Article cannot be identified Valkeinen 2005 Participants too young (mean age of the control group < 60) Van den Ende 2000 Combined program - not PRT alone Vanbiervliet 2003 Included young participants (younger than 60 years old) Veloso 2003 Does not meet the criteria for PRT Verfaillie 1997 Combined program - not PRT alone Villareal 2003 …”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…This procedure was used in three studies [11][12][13] and the results indicated a decrease in the cardiovascular responses. However, some methodological differences were identified that could discharacterize the strength training program, such as a discontinuous series characterized by the inclusion of another exercise 11 ; a too-long interval (15 seconds) and measurement of heart rate, only, which is limited to infer on the cardiovascular demand during the strength training 12 and interval occurring at each repetition 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Segundo os autores, isso pode ser atribuído ao fato de o exercício ter tido dois momentos de início de movimento (retirada da inércia), comprometendo, assim, a utilização da energia elástica muscular e, consequentemente, promovendo uma maior sobrecarga. Já Veloso et al 11 observaram maiores respostas pressóricas durante o exercício realizado de forma contínua. De acordo com Polito et al 10 , diferenças metodológicas podem ter interferido nos resultados, acarretando em respostas distintas.…”
Section: Revisões De Literaturaunclassified